Discovery of a new species of Dryinus (Hymenoptera: Dryinidae) from mid-Cretaceous Burmese amber - Olmi, Massimo; Guglielmino, Adalgisa; Capradossi, Leonardo; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2022)
Dryinus carsteni sp. nov. (Hymenoptera: Chrysidoidea: Dryinidae) is described from mid-Cretaceous Kachin (Burmese) amber. The new species is close to D. taron Martynova, Zhang, Olmi, Müller, Perkovsky, 2020, but it can be distinguished for the shorter body (about 2 mm), antennomere 3 about 5 × as long as broad and protarsomere 2 produced into hook (in D. taron, the body is longer more than 5 mm, antennomere 3 is about 20 × as long as broad and protarsomere 3 is produced into hook).